Sample size estimation revisited - Boreham, C.; Davison, G.; Jackson, R.; Jobson, S.; Wallace, E.; Williams, M. (Journal of Sports Sciences, 2025)
In 2020, we outlined our recommendations on sample size estimation for quantitative studies published in the Journal of Sports Sciences (JSS) (Abt et al., Citation2020), namely, to include a formal a priori sample size estimation and justification and report the full range of information to enable the sample size estimation to be replicated. Following this editorial, Mesquida et al. (Citation2023) reported that when testing a hypothesis only 29% of studies in JSS reported an a priori sample size estimation and that reproducibility of those sample size estimations was suboptimal, with only 9% reporting all necessary inputs to calculations required to reproduce the sample size. However, the data reported by Mesquida et al. (Citation2023) was collected from studies predominately published in 2019 and 2020. The rationale for why calculating and reporting a sample size estimation is not reiterated; for that please read the original editorial (Abt et al., Citation2020) or see Lakens (Citation2022). For the present editorial, we simply report a descriptive audit of recent papers to gauge whether the recommendations made in 2020 are being adopted by the authors.